2007
DOI: 10.2337/dc06-2414
|View full text |Cite
|
Sign up to set email alerts
|

Association of A1C With Cardiovascular Disease and Metabolic Syndrome in Asian Indians With Normal Glucose Tolerance

Abstract: OBJECTIVE -This study examines the association of A1C with cardiovascular disease (CVD) risk factors, coronary artery disease (CAD), and metabolic syndrome in Asian Indians with normal glucose tolerance (NGT). RESEARCH DESIGN AND METHODS-This cross-sectional study recruited subjects from phase III of the Chennai Urban Rural Epidemiology Study (CURES), an epidemiological study in a representative population of Chennai (formerly Madras) in South India, conducted between January 2003 and June 2004. Included were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
25
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 32 publications
(36 reference statements)
7
25
1
Order By: Relevance
“…In Table 2 we can see that Body mass index in all of our patients is significantly correlated to Waist circumference, confirming previous studies [8,10,16]. Therefore BMI and W.C represents good indicators for MS and Insulin resistant patients.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…In Table 2 we can see that Body mass index in all of our patients is significantly correlated to Waist circumference, confirming previous studies [8,10,16]. Therefore BMI and W.C represents good indicators for MS and Insulin resistant patients.…”
Section: Resultssupporting
confidence: 89%
“…Recent studies have shown that the metabolic syndrome increases the risk of cardio vascular disease and diabetes mellitus type II [16]. The NCEP (National Cholesterol Education Program) ATP III guidelines recognized metabolic syndrome as a risk factor for CVD, and this is confirmed by several studies [20].…”
Section: Resultsmentioning
confidence: 90%
“…Linear regression analysis. Dilley et al [20] showed that HbA1c was significantly correlated with the prevalence of CAD. In the same study, HbA1c value of >5.6% predicted CAD with sensitivity and specificities of 56%, 67.6% respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic derangements were reported to worsen continuously with increasing glucose levels, even though the level of fasting glucose was within the normal range ( 10 ). Also, recent studies have reported a linear increase in the risks of diabetes and cardiovascular disease with increasing glucose levels within the normoglycemic range ( 11,12 ).…”
Section: Impact Of Nonalcoholic Fatty Liver Disease On Insulin Resistmentioning
confidence: 99%